Promoting Persuasive Communication Skill through entrepreneurship teaching (Research, Society and Development, 2019)
Entrepreneurship and technological innovation are considered important drivers of socioeconomic development and have therefore been included as a theme in higher education, academic research and university extension. This article aims to analyze the promotion of persuasive communication skills through the teaching of entrepreneurship. Aiming to meet this goal is a dynamic that can be used as a teaching strategy for entrepreneurship in higher education involving the promotion of entrepreneurial skills Persuasive Communication. This is a study based on qualitative research, in which the dynamics developed were applied by three semesters in an undergraduate discipline that addresses management and entrepreneurship. In the form of an experience report, the steps and tasks that make up the dynamics are presented, highlighting the fact that students used different forms of communication to convince potential clients and investors about an innovative idea. The report emphasizes that entrepreneurial skills in persuasive communication can be promoted in the classroom using the aforementioned dynamics, making the class use visual and verbal communication resources to defend business proposals. The study indicates that the dynamics have potential to be applied in disciplines of different areas of knowledge that aim to teach entrepreneurship.